Environmental Management, a modern strategy for sustainable touristic development - FEKIRI, Amel (Journal of Human Sciences, 2020)
The sustainable touristic development is an activity that preserves environment and realizes both economic and social complementarity. It is, indeed, based on the principle of preservation, raising appreciation, giving prominence to  the natural resources and cultural heritage of nations, through embracing ecological behaviors and management style, using innovated technologies to reduce the negative impact of touristic activity, materializing the notion of sustainable tourism through leaning on environment-friendly standards. Tourism institutions, mainly those working in the Hotel sector, are first responsible for protecting tourist areas from the dangers threatening the environment, with regard to the practice of unorganized tourist activities inappropriate to the environment. It is for this reason that comes the project of the environmental management of hotels according to the designation “green hotel”, considered as a modern strategy to fulfill the goals endeavored  by the environmental tourism. It is a kind of touristic works relying on nature, and which aims at reducing the damages of touristic activities on environment in order to achieve a sustainable touristic development.